BARODAK RAPANCAR ON SAMAWAN PEOPLE BALE BRANG VILLAGE - Miftahudin Miftahudin; Arif Sugitanata (Hunafa: Jurnal Studia Islamika, 2020)
This study discusses how the perspective of Islamic law and cultural philosophy and Barodak Rapancar for the Samawa Studi community in Bale Brang Village, Sumbawa Regency. Barodak Rapancar is carried out when someone is going to have a wedding in Bale Brang Village, the couple is scrubbed using a potion commonly referred to by the community as odak, the odak is processed with a mixture of bark from various types of multipurpose trees. The people of Bale Brang believe that if this tradition is not carried out, the family of the bride and groom will experience a form of rabuyak disease. Rabuyak disease namely lumps on the head accompanied by itching, bleeding from the eyes when crying, trance, ribs appearing a few centimeters, and several other strange diseases caused by violating the life cycle ceremony.